2008
DOI: 10.1159/000178145
|View full text |Cite
|
Sign up to set email alerts
|

Imatinib Mesylate Resistance in a Chronic Myeloid Leukemia Patient with a Novel e8a2 BCR-ABL Transcript Variant

Abstract: Background: The vast majority of chronic myeloid leukemia (CML) patients express the BCR-ABL transcript with the b2a2 (e13a2) and/or b3a2 (e14a2) junctions. However, some rare cases have atypical breakpoints. Methods and Results: We identified a CML patient with a unique e8a2 BCR-ABL transcript variant. It contained the first 114 nucleotides of BCR exon 8, with an insertion of 16 nucleotides from the 3′ end of ABL intron 1a, followed by ABL exon 2. Due to her uncontrolled thrombocytosis after 3 years of interf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 17 publications
1
3
0
Order By: Relevance
“…To restore an artificial reading frame between BCR and ABL sequences, two mechanisms were mainly described: i) an intronic insertion of 3n ϩ 1 nucleotides between BCR exon e8 and ABL exon a2, 10,14 or ii) an intronic insertion within exon 8 (formation of an e8 partial/insertion/a2 rearrangement). [11][12][13] Concerning the e8/a2 rearrangement, the same ABL intron Ib inverted insertion has been reported in two CML cases. 10,18 From a technical standpoint, the very low incidence of small sequences inserted within typical e13/a2 or e14/a2 rearrangement in CML could be the consequence of a misidentification of these types of transcript in agarose gel electrophoresis (because of a too small difference in size).…”
Section: Resultssupporting
confidence: 60%
See 1 more Smart Citation
“…To restore an artificial reading frame between BCR and ABL sequences, two mechanisms were mainly described: i) an intronic insertion of 3n ϩ 1 nucleotides between BCR exon e8 and ABL exon a2, 10,14 or ii) an intronic insertion within exon 8 (formation of an e8 partial/insertion/a2 rearrangement). [11][12][13] Concerning the e8/a2 rearrangement, the same ABL intron Ib inverted insertion has been reported in two CML cases. 10,18 From a technical standpoint, the very low incidence of small sequences inserted within typical e13/a2 or e14/a2 rearrangement in CML could be the consequence of a misidentification of these types of transcript in agarose gel electrophoresis (because of a too small difference in size).…”
Section: Resultssupporting
confidence: 60%
“…In most of the cases, the inserted intronic sequence derived from ABL intron Ib (120.1 kb), [7][8][9][10][11] from ABL intron Ia (18.5 kb), 12,13 and more rarely from BCR intron 8 (10.2 kb).…”
Section: Resultsmentioning
confidence: 99%
“…The open reading frame is restored here by the insertion of a sequence being a multiple of 3 bp plus one additional bp (e.g., 111 + 1 bp or 153 + 1 bp), and therefore can produce an oncogenic protein. Several studies identified unusual e8‐[ins]‐a2 transcripts, with various junction types between BCR exon 8 and ABL1 exon 2, most being a 14–55 nucleotide insertion from ABL1 intron 1b (How et al, ; Branford et al, ; Sugimoto et al, ; Cayuela et al, ; Demehri et al, ; Tchirkov et al, ; Park et al, ; Qin et al, ). To our knowledge, only three cases involving a third partner gene have been identified to date (Demehri et al, ; McCarron et al, ; Frederick et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…However, in fewer than 5% of cases, the junction between BCR and ABL1 is unusual, with a breakpoint outside the major BCR (M-BCR) region or with another exon than ABL1 exon 2. Thus, several other fusion transcripts have been identified to date involving breakpoints within exons (Hochhaus et al, 1996;How et al, 1999;Moreno et al, 2001;Demehri et al, 2005;Dessars et al, 2006;van der Velden et al, 2007) or a fragment insertion from an ABL1 intron (Ia or Ib) between BCR exon 8 and ABL1 exon 2 (Branford et al, 2000;Sugimoto et al, 2004;Cayuela et al, 2005;Demehri et al, 2005;Dessars et al, 2006;Park et al, 2008;Qin et al, 2008;Sadia et al, 2010). The majority of these atypical transcripts encode fusion proteins that lack or retain different BCR domains, which could influence the clinical phenotype of the disease.…”
Section: Introductionmentioning
confidence: 99%